2016
DOI: 10.1038/ncomms10494
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analysis uncovers novel loci influencing circulating leptin levels

Abstract: Leptin is an adipocyte-secreted hormone, the circulating levels of which correlate closely with overall adiposity. Although rare mutations in the leptin (LEP) gene are well known to cause leptin deficiency and severe obesity, no common loci regulating circulating leptin levels have been uncovered. Therefore, we performed a genome-wide association study (GWAS) of circulating leptin levels from 32,161 individuals and followed up loci reaching P<10−6 in 19,979 additional individuals. We identify five loci robustl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
189
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(198 citation statements)
references
References 75 publications
7
189
1
1
Order By: Relevance
“…Remarkably, within this list, 7 of the 10 most differentially expressed genes [ME1, secreted protein acidic and cysteine rich (SPARC), MTCH2, LOX, ELOVL5, CAV2, and LEP] are well established in the context of obesity, T2D onset, or adipocyte regulation. ME1 is a known causal obesity gene (45), SPARC is involved with adipocyte differentiation and strongly associated with both obesity and diabetes (46), MTCH2 is a known obesity risk factor gene (47), LOX levels were found altered on bariatric surgery (48), ELOVL5 plays a key role in regulating triglycerides and MUFA/PUFA synthesis (49), genetic polymorphisms in CAV2, in interaction with fat intake, are associated with T2D (50), and LEP is a major hallmark gene in weight loss and obesity (51)(52)(53). Such enrichment in obesity biomarkers lends further credibility to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, within this list, 7 of the 10 most differentially expressed genes [ME1, secreted protein acidic and cysteine rich (SPARC), MTCH2, LOX, ELOVL5, CAV2, and LEP] are well established in the context of obesity, T2D onset, or adipocyte regulation. ME1 is a known causal obesity gene (45), SPARC is involved with adipocyte differentiation and strongly associated with both obesity and diabetes (46), MTCH2 is a known obesity risk factor gene (47), LOX levels were found altered on bariatric surgery (48), ELOVL5 plays a key role in regulating triglycerides and MUFA/PUFA synthesis (49), genetic polymorphisms in CAV2, in interaction with fat intake, are associated with T2D (50), and LEP is a major hallmark gene in weight loss and obesity (51)(52)(53). Such enrichment in obesity biomarkers lends further credibility to our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the serum leptin receptor levels had a correlation with the quantity of the total fat mass has not been confirmed. In the previous studies, researchers demonstrated the significant correlation between serum sOB-R and BMI in a cohort of healthy children and adolescents [26]; and Sun and colleagues showed that the two nonsynonymous SNPs in the LEPR gene were associated with plasma sOB-R levels at the genome-wide significance level, which highlighted and confirmed the role of LEPR as a candidate gene for regulating sOB-R levels [27]. The above conflicting data might reflect variations in the study design and population stratification.…”
Section: Discussionmentioning
confidence: 91%
“…Single nucleotide polymorphisms (SNPs) were identified by first identifying all published genome-wide association studies (GWASs) for leptin and sOB-R. We identified 1 GWAS for circulating leptin (log-transformed ng/mL) [24] and 1 GWAS for sOB-R (log-transformed ng/mL) [25] . All SNPs reported by the authors as having a p value of <5 × 10 -5 after adjusting for age, sex (if applicable), and body mass index (BMI) were considered for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…The GWAS for leptin identified 5 SNPs predictive of leptin levels in 32,161 individuals of European descent from 23 different studies with men ( n = 13,363) and women ( n = 18,698) analyzed separately because of sex differences in circulating leptin [24] . Loci from this first stage were then examined in a sample of 19,979 individuals of European descent from 13 studies.…”
Section: Methodsmentioning
confidence: 99%